2022
DOI: 10.1038/s41598-022-08321-x
|View full text |Cite
|
Sign up to set email alerts
|

E.Co.Tech-electrochemical handheld breathalyzer COVID sensing technology

Abstract: Breathomics is widely emerging as a strategy for non-invasive diagnosis of respiratory inflammation. In this study, we have evaluated the metabolic signals associated with Coronavirus (SARS COV-2), mainly the release of nitric oxide in breath. We have demonstrated the utility of a breath analyzer-based sensor platform for the detection of trace amounts of this target species. The sensor surface is modified with Room Temperature Ionic Liquid (RTIL) that allows faster diffusion of the target gas and can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The property of RTIL has also been applied toward sensing of nitric oxide levels in breath as a marker of respiratory distress, leading to eosinophilic airway inflammation. The authors fabricated a RTIL modified interdigitated electrode for detecting nitric oxide levels in the range of 50–200 ppb as a screen for respiratory inflammation due to COVID-19 infection …”
Section: Electrochemical Detection Of Gases and Vocs With Focus On En...mentioning
confidence: 99%
See 1 more Smart Citation
“…The property of RTIL has also been applied toward sensing of nitric oxide levels in breath as a marker of respiratory distress, leading to eosinophilic airway inflammation. The authors fabricated a RTIL modified interdigitated electrode for detecting nitric oxide levels in the range of 50–200 ppb as a screen for respiratory inflammation due to COVID-19 infection …”
Section: Electrochemical Detection Of Gases and Vocs With Focus On En...mentioning
confidence: 99%
“…Electrochemical biosensors generally utilize chemical interactions such as antibodies/antigens and transduce them into electrical signals utilizing electroanalytical methods. For the application of gas-sensing, Room Temperature Ionic Liquids (RTILs) are used for the modification of electrodes/transducer surfaces to allow adsorption and detection of various gases and VOCs . Other market alternatives to gas-sensing cannot be translated into a portable device or are more costly to implement.…”
mentioning
confidence: 99%
“…Interdigitated electrode array (IDEA) from carbon and metal sources, in contrast, emerges as a favorable electrode biosensor for various health-monitoring and biomedical applications. Indeed, numerous pieces of research highlighting the development of an IDEAs-based biosensor with various detection methods have been extensively reported [ 24 , 25 , 26 ]. Enhanced signal amplification allowing detection of low-concentration bioanalytes displayed by an IDEAs-based biosensor proved to be advantageous for electrochemical biosensing [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, there are some recently published studies presenting the application of FeNO in the risk stratification of COVID-19 patients. 5 Hence, parts per billion-level NO monitoring showed its unique credit in the clinical diagnosis of respiratory disease. Nevertheless, the detection of parts per billion-level NO still remains a big challenge due to the instinctive short half-life and high reactivity of NO molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that fractional exhaled nitric oxide (FeNO, parts per billion level) is a typical biomarker of respiratory inflammation, which is significantly correlated with respiratory diseases such as asthma and chronic cough . Moreover, there are some recently published studies presenting the application of FeNO in the risk stratification of COVID-19 patients . Hence, parts per billion-level NO monitoring showed its unique credit in the clinical diagnosis of respiratory disease.…”
Section: Introductionmentioning
confidence: 99%